Utilization of calprotectin in axial spondyloarthropathies - a review - Tymoszuk, Patrycja; Żak, Agata; Sierzpowski, Rafał; Protasiuk, Agnieszka; Kasperek, Bartosz; Augustowska, Katarzyna; Loryś, Laura; Klimczak, Klaudia (Journal of Education, Health and Sport, 2025)
Introduction and purpose Axial spondyloarthropathies represent a group of chronic inflammatory conditions that primarily affect the joints. Calprotectin, an inflammatory biomarker, is predominantly utilized in the context of inflammatory bowel diseases. This paper aims to explore the potential relationship between calprotectin levels and axial spondyloarthropathies, as well as to discuss how this correlation could be applied in clinical settings. Description Axial spondyloarthritis (axSpA) is a chronic inflammatory disorder that primarily impacts the sacroiliac joints and the spine, leading to symptoms such as inflammatory back pain and stiffness. The etiopathogenesis of axSpA is complex and multifactorial, involving genetic factors like HLA-B27 and immune system dysregulation. Recently, calprotectin has emerged as a significant inflammatory biomarker, showing promise in relation to axSpA. Elevated calprotectin levels have been associated with increased disease activity, indicating its potential utility in monitoring inflammation and influencing treatment strategies. Nevertheless, the precise role of calprotectin in the pathogenesis and progression of axSpA remains unclear, necessitating further research to establish its clinical relevance. Summary Although axial spondyloarthritis is a condition that can be effectively managed, its chronic nature, along with symptoms like inflammatory back pain and stiffness, can significantly affect the quality of life for patients and induce anxiety in patients and their families. The exploration of biomarkers such as calprotectin presents a promising opportunity for assessing disease activity and informing treatment strategies; however, its precise role remains unclear. Advancing research into calprotectin's involvement in axSpA is essential for developing innovative strategies for disease prevention, enhancing diagnostic accuracy, and deepening our understanding of the inflammatory mechanisms that underlie this condition.